2018
DOI: 10.1016/j.nano.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

HER2-targeted gold nanoparticles potentially overcome resistance to trastuzumab in gastric cancer

Abstract: An issue of concern is that no current HER2-targeted therapeutic agent is effective against Trastuzumab (Tmab)-resistant gastric cancer. Gold nanoparticles (AuNPs) are promising drug carriers with unique characteristics of a large surface area available for attachment of materials such as antibodies. Here, we created HER2-targeted AuNPs (T-AuNPs) and examined their therapeutic efficacy and cytotoxic mechanisms using HER2-postive Tmab-resistant (MKN7) or Tmab-sensitive (NCI-N87) gastric cancer cell lines. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…While most conjugates in the literature use some variation of this amide bond formation involving lysines on the antibody, a PEG linker terminated in a hydrazide can be used, which allows for the cross-linking of AuNPs with carboxylic acids on the surface of antibodies. 73 This chemistry, while utilising different residues on the antibody is still completely random and may lead to even more variations as there are on average more carboxylic acids present on antibodies than amines. 74 While antibodies display high affinity towards their target, this affinity relies on the antigen binding sites remaining nonfunctionalised and unhindered.…”
Section: Igg Antibodiesmentioning
confidence: 99%
“…While most conjugates in the literature use some variation of this amide bond formation involving lysines on the antibody, a PEG linker terminated in a hydrazide can be used, which allows for the cross-linking of AuNPs with carboxylic acids on the surface of antibodies. 73 This chemistry, while utilising different residues on the antibody is still completely random and may lead to even more variations as there are on average more carboxylic acids present on antibodies than amines. 74 While antibodies display high affinity towards their target, this affinity relies on the antigen binding sites remaining nonfunctionalised and unhindered.…”
Section: Igg Antibodiesmentioning
confidence: 99%
“…Subcutaneous tumors were formed after subcutaneous injection of MKN1-Luc, KATO III, and MKN45-Luc cells. Previous reports have shown that N87, NUGC4 and OCUM-1 can form subcutaneous tumors in nude mice (14)(15)(16)(17)(18).…”
Section: Resultsmentioning
confidence: 98%
“…For example, Sharma et al (2008) have chemically conjugated anti-HER2 to CpG, which has led to tumor eradication and induction of protective memory when combined with anti-GITR immunotherapy. In addition, tumor-targeting antibodies have been conjugated to material surfaces, such as nanoparticles (Kubota et al, 2018) or liposomes (Espelin et al, 2016), to confer them the ability to target tumors. Interestingly, biological cell-based materials can be similarly engineered; for instance, in the context of chimeric antigen receptor (CAR)-T cell therapies, patient-derived T lymphocytes are transduced with a modified TCR that comprises a scFv fragment recognizing a specific cancer antigen (Jackson et al, 2016).…”
Section: Targeting the Cancer Cell Surface (Figure 4a)mentioning
confidence: 99%